Penggunaan Metode Simpleks dalam Memaksimalisasi Keuntungan pada Usaha Dagang Martabak Telur Brebes serta Implementasinya pada POM – QM dan R Studio - Sulfiyandi Sulfiyandi; Ayu Indryani; Pradita Eko Prasetyo Utomo (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2023)
The purpose of this research is to determine the maximum profit in the business of making martabak in one day. This research was conducted at the Martabak Stall located in front of the University of Jambi's gate. The martabak trading business produces two types of martabak daily: regular egg martabak and special egg martabak. This research uses the simplex method to find the maximum profit for this martabak business. The result of this research is that the maximum profit obtained in one day is Rp 75.000,- so it can be concluded that the simplex method is suitable for finding the optimum solution.